Why children die: avoidable factors associated with child deaths. - Pearson, G; Ward-Platt, M; Harnden, A; Kelly, D (2011)
AIM: To describe the avoidable factors associated with child deaths identified by a confidential enquiry. METHOD: In the Centre for Maternal and Child Enquiries confidential enquiry, a sample (13%) of cases was subjected to case note review by multidisciplinary panels attempting to identify avoidable factors associated with the deaths. Cases were selected blindly but in equal numbers from predetermined age bands and participating regions. The anonymised records were reviewed in regions remote to where the child lived and died. Panel composition, conduct and reporting were standardised. RESULTS: 119 of 126 cases reviewed by enquiry panels had sufficient information to determine avoidable factors. These cases were comparable with the whole dataset in terms of sex and causes of death. 31 (26%) of 119 had avoidable factors that were predominantly related to individuals or agencies with a direct responsibility to the child. 51 (43%) of 119 were defined as potentially avoidable. In all, 130 factors were considered in relation to these 82 cases, and 64% of the factors were healthcare related. Avoidable factors were more likely where life-limiting illness was not present. Recurring avoidable factors included failure to recognise serious illness at the point of presentation and death occurring in children who had been lost to follow-up. CONCLUSION: Child Death Overview Panels now have the responsibility to review child deaths using similar methods but relying upon data forms rather than the case record. Analysis of contributory factors on a national scale has the potential to improve understanding of why children die and indicate strategies to reduce child mortality.